PENANGGUHAN EKSEKUSI TERHADAP PERKARA KASASI NOMOR 517 K/PDT/2022 KARENA ADANYA UPAYA PENINJAUAN KEMBALI PADA MAHKAMAH AGUNG REPUBLIK INDONESIA - Mesi Arianti, YUNIMAR dan (Fakultas Hukum Universitas Tamansiswa Padang, 2024)
Legal remedies for a request for judicial review in principle do not suspend the implementation of the decision. Article 66 paragraph (2) of Law Number 14 of 1985 concerning the Supreme Court states